Association between depression and endometriosis using data from NHANES 2005–2006 - Pan-Wei Hu; Xiao-Le Zhang; Xiao-Tong Yan; Cong Qi; Guo-Jing Jiang (Scientific Reports, 2023)
Abstract Studies on the association between depression and self-reported endometriosis are limited, and further studies are required to investigate this association. Data were collected from the National Health and Nutrition Examination Survey database (2005–2006). Based on the inclusion and exclusion criteria, 100 participants with self-reported endometriosis and 1295 participants without self-reported endometriosis were included, representing a total population of 64,989,430. Depression severity was assessed using the Patient Health Questionnaire 9 (PHQ9). A survey-weighted logistic regression analysis was performed to explore the association between depression and endometriosis. Subgroup analyses were conducted to explore heterogeneity. The prevalence of endometriosis was 7.17%. A significant positive association was found between the PHQ9 score and endometriosis. After adjusting for all covariates, the PHQ9 score positively correlated with endometriosis. Furthermore, compared with the participants without depression, those with moderate depression were more prone to have endometriosis both in unadjusted and fully adjusted model. However, the relationship between severe depression and endometriosis was not significant in all models (P > 0.05). Our findings highlight the influence of depression on the prevalence of self-reported endometriosis. Further studies are required to elucidate the causal relationship between depression and self-reported endometriosis.